The Difficulties Of Argumentative Essay Writing Experienced By Undergraduate Students Of English Department Mulawarman University - Yohanisa Septyana; Aridah Aridah; Ida Wardani (English Department, Faculty of Teacher Training and Education, Mulawarman University, 2021)
The purpose of this study was to find out the difficulties faced by the undergraduate students in writing argumentative essay and their strategies to solve their difficulties. The design of this study was qualitative case study that aims in understanding and explaining the difficulties faced by the undergraduate students of English Department Mulawarman University in writing argumentative essay. The subject of this study was the seventh semester students of English Department Mulawarman University in academic year 2019/2020. The data were collected from students’ argumentative essay writing task and semi-structured interview. The result of the study showed that the students faced difficulties in linguistic, cognitive, and psychological aspect when writing argumentative essay. The most dominant difficulties in linguistic aspects were grammar, finding the correct diction, and in linking paragraph. Then, idea organization was claimed as the most difficult thing in cognitive aspect. Moreover, in psychological aspect the students mentioned stress and laziness. Based on those mentioned difficulties they had their strategies: they used the internet to search about the explanations of the given topic and examples of the correct punctuation and connector. In addition, they used the dictionary to find the correct diction and synonym of a word. Revising and translating were also mentioned as their strategies to solve difficulties in spelling and sentence structure.